Design Considerations of a Liquid Krypton Detector of Gamma Rays Below 12 MeV - Koltick, D. S.; Hosack, M. G. (IEEE transactions on nuclear science, 2013)
Liquid krypton has been used widely for electromagnetic calorimeters for charged particle and gamma ray detection above 100 MeV. Despite the significant price advantage of krypton over xenon, little work has been done with liquid krypton detectors for energies in the range 200 keV-12 MeV that is useful for applications involving neutron-induced gamma ray spectral analysis for isotope identification in elemental analysis. The presence of β decays arising from 85 Kr (10.76-year half-life) combined with the 80 ns decay time of the dominant component of krypton scintillation light generates pile-up and reduces the photopeak efficiency of liquid Kr detectors. We discuss detector performance expected after careful optimization of the detector dimensions and doping the Kr with Xe to improve its scintillation light decay time characteristics.